2017
DOI: 10.1016/j.lungcan.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a telephone-based smoking cessation intervention in the lung cancer screening setting: A randomized clinical trial

Abstract: Incorporating effective smoking cessation interventions into lung cancer screening (LCS) programs will be essential to realizing the full benefit of screening. We conducted a pilot randomized trial to determine the feasibility and efficacy of a telephone-counseling (TC) smoking cessation intervention vs. usual care (UC) in the LCS setting. In collaboration with 3 geographically diverse LCS programs, we enrolled current smokers (61.5% participation rate) who were: registered to undergo LCS, 50–77 years old, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 49 publications
1
65
0
Order By: Relevance
“…Finally, a pilot study recently reported on shortterm (3-month) quit rates in 92 screening participants randomized to a telephone counseling intervention similar to ours versus usual care and noted similar selfreported quit rates (21.7% vs. 19.6%), although biochemically confirmed quit rates were higher (17.4% vs. 4.3%). 36 Attempts at integrating smoking cessation with cervical cancer screening has had mixed success. 16,37,38 The difficulty in showing increased smoking cessation rates in screening programs through the application of interventions otherwise considered effective requires further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a pilot study recently reported on shortterm (3-month) quit rates in 92 screening participants randomized to a telephone counseling intervention similar to ours versus usual care and noted similar selfreported quit rates (21.7% vs. 19.6%), although biochemically confirmed quit rates were higher (17.4% vs. 4.3%). 36 Attempts at integrating smoking cessation with cervical cancer screening has had mixed success. 16,37,38 The difficulty in showing increased smoking cessation rates in screening programs through the application of interventions otherwise considered effective requires further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the advice was tailored to smoking attitudes and behaviour but not to understanding of and emotional response to screening test results. A telephone counselling intervention which aimed to use lung cancer screening test results to increase risk perceptions was effective at promoting cessation in a pilot randomised trial [ 20 ]. The stated aim of this strategy was to capitalise on the teachable moment of an abnormal result and to counteract the potential for reduced motivation to quit after a result showing no nodules or abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies on smokers undergoing LCS without any formal SC program reported that 22% had stopped smoking two months after screening [117][118][119][120][121][122], 8% had stopped after six months [123], and 14% were found, by biochemical assay, to be non-smokers a year after screening [124,125]. Ten studies reported outcomes of help given to all smokers undergoing screening [126][127][128][129][130][131][132][133][134][135].…”
Section: Interventions To Stop Smokingmentioning
confidence: 99%
“…No differences were found for standard written self-help materials vs. a list of internet SC resources [136], tailored vs. standard written SC information [137], or a brief SC counselling session on the day of screening vs. self-help printed materials and quit-line details [138]. One study testing the efficacy of six telephone-based services delivered by trained counsellors vs. self-help SC resources reported significantly higher biochemically verified 7-day point prevalent quit rates at 3-month follow-up vs. control (17.4% vs. 4.3%) [120]. One small study reported 57% abstinence for more than six months after cognitive-behaviour therapy therapy (CBT) and pharmacotherapy [122]; another study reported 20% biochemically validated continuous abstinence for one year in smokers who received four sessions of CBT-based telephone counselling by a psychologist and 12 weeks of pharmacotherapy with varenicline [119].…”
Section: Interventions To Stop Smokingmentioning
confidence: 99%